Peningkatan Produksi dan Daya Saing Kopi di Desa Sumanding Kecamatan Kembang Kabupaten Jepara - Sagaf, M.; Syakhroni, Akhmad (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
One of the coffee farmers and processors in the Kembang Jepara district, Mr. Eko Siswanto, made a business called Vinzoei with coffee products branded The Boyo (Mitra), which has problems in the field of low production capacity. This is because partners process coffee using third-party services, which causes long queue times and high production costs. The product packaging design is still very traditional and unattractive. To overcome these problems, the methods used include outreach, mentoring, monitoring, and evaluation. The results of the increase in benefits from this regional partnership program are an increase in production capacity by 25%, an increase in coffee quality control knowledge by 100%, an increase in assets in the form of a grinder tool by 100%, an increase in product packaging design by 100%, an increase in knowledge about good business management by 100%.